The contribution of interleukin-2 to effective wound healing - Doersch, Karen M (Exp Biol Med (Maywood), 2016)
Ineffective skin wound healing is a significant source of morbidity and mortality. Roughly 6.5 million Americans experience chronically open wounds and the cost of treating these wounds numbers in the billions of dollars annually. In contrast, robust wound healing can lead to the development of either hypertrophic scarring or keloidosis, both of which can cause discomfort and can be cosmetically undesirable. Appropriate wound healing requires the interplay of a variety of factors, including the skin, the local microenvironment, the immune system, and the external environment. When these interactions are perturbed, wounds can be a nidus for infection, which can cause them to remain open an extended period of time, or can scar excessively. Interleukin-2, a cytokine that directs T-cell expansion and phenotypic development, appears to play an important role in wound healing. The best-studied role for Interleukin-2 is in influencing T-cell development. However, other cell types, including fibroblasts, the skin cells responsible for closing wounds, express the Interleukin-2 receptor, and therefore may respond to Interleukin-2. Studies have shown that treatment with Interleukin-2 can improve the strength of healed skin, which implicates Interleukin-2 in the wound healing process. Furthermore, diseases that involve impaired wound healing, such as diabetes and systemic lupus erythematosus, have been linked to deficiencies in Interleukin-2 or defects Interleukin-2-receptor signaling. The focus of this review is to summarize the current understanding of the role of Interleukin-2 in wound healing, to highlight diseases in which Interleukin-2 and its receptor may contribute to impaired wound healing, and to assess Interleukin-2-modulating approaches as potential therapies to improve wound healing.